Management of nasal septal perforation using silicone nasal septal button - Mullace, M (Pacini Editore SpA, 2006)
Nasal septal perforation may present with various symptoms: epistaxis, crusting, secondary infection, whistling and nasal obstruction. Perforation may be treated by conservative pharmacological treatment or closed by surgical approach. A useful alternative is mechanical obturation, achieved inserting a prosthesis. The present report refers to a study on 15 patients (10 male, 5 female, mean age 38.5 years) treated by insertion of a one-piece or two-piece silicone septal button (Xomed). In the follow-up period, insertion of the nasal button reduced epistaxis, eliminated whistling during inspiration, and reduced nasal obstruction and crusting around the margin of the perforation. Contraindications are presence of acute infection with osteitis, chronic septal disease (Wegener), neoplasia and extremely large perforations. The latest buttons appear to be superior to the conventional type on account of plasticity and adaptability which offer greater conformity to the septum. This study also reveals that the new septal button is well tolerated by patients.